Optimization of Social Media Campaigns: Applying CRO in Digital Advertising - García-Martínez, María-Ester; Rodríguez-Valero, Daniel; Olivares-Delgado, Fernando (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
This study analyzes the application of conversion rate optimization (CRO) techniques in social media advertising campaigns, exploring how visual alignment with competitor brands influences user interaction. Through a case study in the footwear sector, Meta Ads were evaluated, and predominant visual patterns were identified. Findings suggest that consistency with industry trends can reduce conversion friction, optimizing advertising effectiveness. This approach reinforces the need to integrate CRO strategies from the user acquisition stage, improving user experience and increasing commercial performance.